2015
DOI: 10.1557/opl.2015.822
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Tungsten Inert Gas Pulsed Welding Applied to Ni-Ti Shape Memory Alloy Wires

Abstract: Shape memory alloys are functional materials that can recover plastic strains between 2 and 6%. This property can be used to produce actuators for many areas as medicine, robotic, aeronautic and others. Recently, it has been observed the particular interest for shape memory alloys welding, especially to obtain Ni-Ti similar and dissimilar joints and fabricate simple or complex structures. In this sense, this work present an experimental study of tungsten inert gas pulsed welding applied to Ni-Ti shape memory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Using LTT welding filler, weld toe treatment using TIG dressing has been shown to be capable of improving the fatigue properties of welded joints to some degree [8,9]. In addition, it is found that TIG welding has a great influence on phase transformation behavior and mechanical properties of welded joints [10]. As aforementioned, LTT welding filler does well in fatigue performances but poorly in toughness [6].…”
Section: Introductionmentioning
confidence: 93%
“…Using LTT welding filler, weld toe treatment using TIG dressing has been shown to be capable of improving the fatigue properties of welded joints to some degree [8,9]. In addition, it is found that TIG welding has a great influence on phase transformation behavior and mechanical properties of welded joints [10]. As aforementioned, LTT welding filler does well in fatigue performances but poorly in toughness [6].…”
Section: Introductionmentioning
confidence: 93%